Self-assessment of striae gravidarum prophylaxis - Antoszewski, Bogusław; Sobczak, Małgorzata; Kasielska-Trojan, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Striae are the most frequently occurring pathology of connective tissue during pregnancy. According to the statistical data, 70–90% of women suffer from striae gravidarum. Aim: To assess effectiveness of topical products and massage used by pregnant women in striae gravidarum prophylaxis. Material and methods : The questionnaire study was conducted among 299 women who were maximum 6 months after delivery at term. The questionnaire included questions concerning age, occurrence of striae gravidarum during pregnancy, their location, week of gestation when the lesions appeared and used striae prophylaxis as well as its effectiveness in respondents’ opinion. Results : Analysis of the correlation between striae gravidarum occurrence and use of different types of cosmetics showed that this kind of prophylaxis is effective when applied at least twice a day (63.7% vs. 77.6%). No correlation between the type of cosmetics and presence of striae was observed (p > 0.05). Conclusions : Use of prophylactic measures like skin emollients and oils with the appropriate frequency significantly reduces the risk of striae gravidarum occurrence.